2016
DOI: 10.17221/112/2015-agricecon
|View full text |Cite
|
Sign up to set email alerts
|

Agriculture and Environmental Kuznets Curves in the case of Turkey: evidence from the ARDL and bounds test

Abstract: Th e paper empirically analyses the long run relationship between agricultural performance and the carbon dioxide emission in Turkey by using the annual data covering . Th e Bounds test approach for the co-integration and ARDL (Autoregressive Distributed Lag) method are employed to show the existence of long-term relationship between the carbon dioxide emission and its determinants in this country. Th e results consistent with the Environmental Kuznets Curves (EKC) hypothesis show that the real GDP has a signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(17 citation statements)
references
References 17 publications
2
14
1
Order By: Relevance
“…Moreover, we found that after taking the first lag of agricultural value-added, its effect on CO 2 emissions was negative, indicating that the historical effects of agricultural value-added underpin CO 2 emissions mitigation. The negative relationship between agriculture and CO 2 emissions is supported by a finding documented for 53 countries in the world (Rafiq et al, 2016); five MENA countries (Ben Jebli and Ben Youssef, 2017), and Turkey (Dogan, 2016). Furthermore, the influence of biocapacity on CO 2 emissions is negative, inelastic and substantial in the long run while in the short run, it is negative, elastic and significant.…”
Section: Ardl Estimated Resultsmentioning
confidence: 71%
See 2 more Smart Citations
“…Moreover, we found that after taking the first lag of agricultural value-added, its effect on CO 2 emissions was negative, indicating that the historical effects of agricultural value-added underpin CO 2 emissions mitigation. The negative relationship between agriculture and CO 2 emissions is supported by a finding documented for 53 countries in the world (Rafiq et al, 2016); five MENA countries (Ben Jebli and Ben Youssef, 2017), and Turkey (Dogan, 2016). Furthermore, the influence of biocapacity on CO 2 emissions is negative, inelastic and substantial in the long run while in the short run, it is negative, elastic and significant.…”
Section: Ardl Estimated Resultsmentioning
confidence: 71%
“…In this study, we incorporated agricultural and biocapacity variables into the standard EKC framework. This is because, agricultural activities and biocapacity of a country could contribute or mitigate the rate of carbon emissions as documented in the earlier studies by Dogan (2016), . Therefore, our model will be expressed as follows:…”
Section: Model Specificationmentioning
confidence: 84%
See 1 more Smart Citation
“…For example, the Rodale Institute, led by David Pimental, a well-known professor of ecology at Cornell University, conducted the Farming System Trial on three plots-a traditional intensive agriculture (fertilizers) plot, an organic agriculture (manure) plot, and a legume rotation organic agriculture (plant nitrogen fixation) plot-to analyze the differences in energy input, soil organic matter, water quality, biological resources, production level, and labor input from 1981 to 2002. This experiment provided important data for estimating the potential of agricultural carbon emission reduction and analyzing the cost of emission reduction from an economic perspective [25].…”
Section: Introductionmentioning
confidence: 99%
“…Besides, the perspective of input-output, which takes electricity consumption into consideration, has been used by some scholars to measure the agricultural carbon emissions in Chongqing [23]. Recently, further research has been undertaken on the carbon emissions of livestock and poultry, including cows, sheep, goats, pigs, chickens, and ducks [24,25].…”
Section: Introductionmentioning
confidence: 99%